Application of Vehicle Restraint Systems (VRSs) in the State of Qatar: A Case Study from Northern Roads - Muley, Deepti; Tahmasseby, Shahram; Wink, Bernd Wolfgang; Tarlochan, Faris (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Recent developments within Infrastructural Road Safety and especially in the Sector of Vehicle Restraint Systems (VRS) have enabled Transport Authorities to significantly reduce road fatalities and severe injuries. Predominantly, two authorities have established leading guidelines for VRS installation and maintenance, - the European Union (EU) and the United States. The guidelines for the State of Qatar are based on these two sources. This technical paper briefly reviews the aforementioned guidelines, highlights the additional items in the EU guidelines, and explains the evolution of the State of Qatar guidelines accordingly. Moreover, this paper explains the application of VRS guidelines to the road network of the State of Qatar by presenting evidences from a recent site visit to the highways/expressways in the Northern Part of the Qatari Road Network. The outcomes of the site visit mainly highlight the typical steel VRS applied alongside the road (lateral as well as in central reserve, median), crash cushions, and various terminal systems. The paper is aiming to support designers, planners, auditors, contractors and installers to improve road safety from the VRS point of view.